If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+3(2x-1)=-2(5x-6)+4x
We move all terms to the left:
5+3(2x-1)-(-2(5x-6)+4x)=0
We multiply parentheses
6x-(-2(5x-6)+4x)-3+5=0
We calculate terms in parentheses: -(-2(5x-6)+4x), so:We add all the numbers together, and all the variables
-2(5x-6)+4x
We add all the numbers together, and all the variables
4x-2(5x-6)
We multiply parentheses
4x-10x+12
We add all the numbers together, and all the variables
-6x+12
Back to the equation:
-(-6x+12)
6x-(-6x+12)+2=0
We get rid of parentheses
6x+6x-12+2=0
We add all the numbers together, and all the variables
12x-10=0
We move all terms containing x to the left, all other terms to the right
12x=10
x=10/12
x=5/6
| 3w=6w+5 | | -18+32r=18 | | 1/x=x/3 | | -7(z+6)=49 | | 20=18-x/2 | | 69x=61x | | 20=18–xx/2 | | y/8+40=43 | | 3x+15+55+90=180 | | 3x/18×2x/18=10 | | 3x+-2(3x+2)=8 | | 21x+32=98 | | -3.5=r-8.3 | | −13x−2=−10x−2 | | 3=2b−3 | | 9x+35+90=180 | | 26−10b=-14 | | -8x-2(2-3x)+6-6(4-8x)=13(4x+9)-4(5x-2)+10 | | x+12+58+90=180 | | 14x-84=-1x-1 | | 3x-7=154 | | 20=18–x2 | | 4z−3=13 | | x-100=-9 | | 3240r=30 | | x(-8)=72 | | 7+2g=11 | | 17=r/3+ 13 | | x-(-2)=47 | | -150+(-45x)+5x^2=0 | | 17=r3+13 | | 9f=8 |